Labor Analgesia reduces the risk of postpartum depression: A cohort study - Ren Li (De Gruyter, 2021)
Postpartum depression (PPD) is a frequent mental disorder after delivery. In China, most parturients give birth with the assistance of labor analgesia (LA) or by cesarean section (CS); however, it is still unclear whether these two approaches reveal different effects on PPD.